Новини прайм-тайму провідних українських телевізійних каналів напередодні президентських виборів: результати моніторингу новин – березень 2019 р. - Костенко, Наталія; Іванов, Валерій Феліксович (Київський національний університет імені Тараса Шевченка, 2019)
Академія української преси з 2002 р. за участю вчених Інституту соціології НАН України проводить дослідження новин прайм-тайму провідних українських телеканалів. Моніторинг проводиться методом контент-аналізу, тобто кількісного методу вивчення документів, який характеризується строгістю процедури і надійністю висновків та полягає у квантифікаційній обробці тексту з подальшою інтерпретацією результатів. У статті розглядаються основні тенденції, які були зафіксовані при аналізі новин прайм-тайму за березень 2019 року: Політичні новини в Україні у фокусі уваги програм березня. Основне джерело інформації – власні кореспонденти. Увага до президентських виборів зросла з 18% до 22% в порівнянні з новинами лютого 2019 р. Канали неоднорідні за часткою уваги до теми виборів-2019. В новинах згадувалися 17 кандидатів у президенти з 44. Найвища увага в новинах до політиків-кандидатів П.Порошенка, Ю.Тимошенка, О.Ляшка, О.Вілкула, Ю.Бойка. Канали помітно сегментовані за своїми політичними преференціями, неухильно додержуються власних стратегій виборчої кампанії.

The Academy of Ukrainian Press since 2002, with the participation of scientists of the Institute of Sociology of the NAS of Ukraine, conducts research of prime time news (19:00-23:00) of the leading Ukrainian TV channels. Monitoring is carried out by content analysis, that is, a quantitative method of document study, characterized by rigor of the procedure and reliability of conclusions, and consists in quantitative processing of the text with subsequent interpretation of the results. The article looks at the main trends that were identified in the March 2019 Prime Time News Analysis: Political news in Ukraine focuses on March programs. Only 1+1 is traditionally dominated by all other news about Ukraine. The intensity of attention to political news varies markedly. The main source of information is media’s own correspondents. Attention to the presidential election increased from 18% to 22% compared to February 2019 news. Channels are heterogeneous in their focus on the 2019 election theme. Every third announcement on Ukraine on Inter, Ukraine, ICTV channels is electionrelated; each eleven on the 1st and twelve on the 5th. In the news, 17 presidential candidates were mentioned out of 44 registered by the CEC (39%, in February 34%). The most frequently reported was the campaign of Yulia Tymoshenko, O. Vilkul, P. Poroshenko, and O. Lyashko. The highest attention in the news to the candidate politicians P.Poroshenko, Y.Tymoshenko, O.Lyashko, O.Vilkul, Y.Boyko. Only in a positive and neutral context was A. Gritsenko mentioned, and in the least ironic and negative about Y. Boyko and Y. Tymoshenko. The most frequently mentioned in the ironic and negative are Yuri Tymoshenko and E. Muraev. P. Poroshenko, O. Vilkul, O. Lyashko, Y. Tymoshenko, and Y. Boyko had more time in the news. For two months in a row V. Zelensky has been in sync only in 1+1 news. Channels are markedly segmented by their political preferences, adhering strictly to their own election campaign strategies.
Prime time news of the leading Ukrainian TV channels ahead of the presidential elections: News monitoring results – March 2019
Keywords: content analysis; leading TV channels; election media strategies; ratings of attention; policy synchronous ratings; контент-аналіз; провідні телеканали; виборчі медіастратегії; рейтинги уваги; рейтинги синхрону політиків